2020
DOI: 10.1007/s41347-020-00177-0
|View full text |Cite
|
Sign up to set email alerts
|

Social Skills Training for Autism Spectrum Disorder: a Meta-analysis of In-person and Technological Interventions

Abstract: Social skills training (SST) for autism spectrum disorder (ASD) has traditionally focused on face-to-face (F2F-SST) interventions. Recently, Behavioral Intervention Technologies (BITs-SST) have been utilized to target social skills deficits using computer-based programs, avatars, and therapeutic robots. The present meta-analysis reviews recent evidence and compares the efficacy of 14 F2F-SST and four identified BITs-SST intervention trials for youth with ASD. These preliminary analyses did not indicate signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(50 citation statements)
references
References 66 publications
1
43
0
6
Order By: Relevance
“…Differences between the two stimuli are particularly important since a combined use of face-to-face and technological interventions has been suggested (Soares et al, 2021), thus it is worth investigating how the two types of stimuli can influence visual processes and promote attention to particular aspects of the social stimulus since social information encoding seems to be of particular relevance in the social cognition of children with ASC (Pino et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Differences between the two stimuli are particularly important since a combined use of face-to-face and technological interventions has been suggested (Soares et al, 2021), thus it is worth investigating how the two types of stimuli can influence visual processes and promote attention to particular aspects of the social stimulus since social information encoding seems to be of particular relevance in the social cognition of children with ASC (Pino et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, many rehabilitative interventions use technology such as robots, avatars and virtual environments to teach new skills to children with ASC (Orvalho et al, 2009;Jarrold et al, 2013;Bekele et al, 2014;Aresti-Bartolome & Garcia-Zapirain, 2015;Lahiri et al, 2015;Newbutt et al, 2016;Liu et al, 2017;Elgarf et al, 2017;Shoaib et al, 2017;Papathomas & Goldschmidt, 2017;Ravindran et al, 2019;Yuan & Ip, 2018;Khowaja et al, 2019;Valencia et al, 2019;Rojo et al, 2019;Herrero & Lorenzo, 2020;Di Mascio et al, 2020). Soares et al (2021) conducted a meta-analysis comparing randomized controlled trials of face-to-face and technological interventions for children and adolescents with autism to improve social skills. These interventions included the use of computer-based software, computer avatars and therapeutic robots and found that both types of intervention resulted in comparable improvements in social skills.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the brief but intensive nature of the summer programs (2019-in-person;2020-Online), attendance to all sessions was calculated. Conversely, a three-month period was assessed for each of the school year programs (20192019-2021. Doing so kept the number of sessions and time duration per sample relatively balanced.…”
Section: Program Analysis Attritionmentioning
confidence: 99%
“…(f) Support in the rehabilitation therapy of communication disabilities such as autism or others, where the robot can represent a useful tool full of stimuli for children [18,[21][22][23][24][25][26][27][28].…”
Section: Social Robotsmentioning
confidence: 99%
“…Here, Sheridan [23] makes the important consideration that for user acceptance, government regulator acceptance and sales appeal, engineering/research related to social psychological and human factors should be applied to social robots. This is especially true for children's toys because children are the most vulnerable of the various user categories.…”
Section: Toys and The Market For Social Robots In Generalmentioning
confidence: 99%